Perlakuan Hukum terhadap Barang Bawaan Penumpang di Bandara Internasional Sultan Iskandar Muda: Suatu Kajian Socio-Legal - Efendi. A, Edi; Rahmah, Siti; Aidy, Zul (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2025)
The legal treatment of passenger baggage at Sultan Iskandar Muda International Airport in Banda Aceh is a crucial issue in customs and public protection. The Directorate General of Customs and Excise (DJBC) is responsible for collecting taxes and protecting the public from dangerous goods. The increase in smuggling indicates a lack of understanding among passengers regarding applicable legal provisions. Many passengers assume that goods for personal use are tax-free, but in fact, there are value limits that must be understood. This study aims to identify legal provisions regarding passenger baggage from within and outside the country, as well as sanctions for violations. The method used is sociological legal research, with data collection through field observations and literature studies. The results show that legal provisions are regulated in Law No. 1 of 2009 concerning Aviation and No. 17 of 2006 concerning Customs. Administrative and criminal sanctions serve as a deterrent effect. Factors such as financial literacy and outreach from airlines contribute to passenger understanding. Better education from authorities is essential to reduce the risk of disputes and improve the travel experience. [ Perlakuan hukum terhadap barang bawaan penumpang di Bandara Internasional Sultan Iskandar Muda Banda Aceh merupakan isu penting dalam kepabeanan dan perlindungan masyarakat. Direktorat Jenderal Bea dan Cukai (DJBC) bertanggung jawab untuk memungut pajak dan melindungi masyarakat dari barang berbahaya. Meningkatnya penyelundupan menunjukkan kurangnya pemahaman penumpang mengenai ketentuan hukum yang berlaku. Banyak penumpang mengira barang untuk keperluan pribadi bebas pajak, padahal ada batasan nilai yang harus dipahami. Penelitian ini bertujuan untuk mengidentifikasi ketentuan hukum mengenai barang bawaan penumpang dari dalam dan luar negeri, serta sanksi terhadap pelanggaran Metode yang digunakan adalah penelitian hukum sosiologis, dengan pengumpulan data melalui observasi lapangan dan studi pustaka. Hasil penelitian menunjukkan bahwa ketentuan hukum diatur dalam Undang-Undang No. 1 Tahun 2009 tentang Penerbangan dan No. 17 Tahun 2006 tentang Kepabeanan. Sanksi administratif dan pidana berfungsi sebagai efek jera. Faktor seperti literasi keuangan dan sosialisasi dari maskapai berkontribusi terhadap pemahaman penumpang. Edukasi yang lebih baik dari pihak berwenang penting untuk mengurangi risiko sengketa dan meningkatkan pengalaman perjalanan.]